Voice into acting : integrating voice and the Stanislavski approach - Gutekunst, Christina; Gillett, John (London, England : Zed Books, 2021)
"How can actors bridge the gap between themselves and the text and action of a script, integrating fully their learned vocal skills? How do we make an imaginary world real, create the life of a role, and fully embody it vocally and physically so that voice and acting become one? Christina Gutekunst and John Gillett unite their depth of experience in voice training and acting to create an integrated and comprehensive approach informed by Stanislavski and his successors - the acting approach widely taught to actors in drama schools throughout the world. This updated edition contains: a new section on vocal embodiment of actions, new findings from neuroscience as evidence of the science behind the approach, more exercises and warm-up routines for training, pre-rehearsal and pre-performance. The authors create a step-by-step guide to explore how voice can: - Respond to our thoughts, senses, feelings, imagination and will - Fully express language in content and form - Communicate imaginary circumstances and human experience - Transform to adapt to different roles - Connect to a variety of audiences and spaces Featuring 55 illustrations by German artist, Dany Heck, Voice into Acting is an essential manual for the actor seeking full vocal identity in characterization, and for the voice teacher open to new techniques or an alternative approach to harmonize with the actor's process"--
What Practitioners Said about the First Edition Introduction Part I: Laying the Foundations 1. The Organic Acting Approach and the Voice 2. The Organic Acting Approach and the Brain Part II: The Essential Vocal Six ? And Integrating Acting into Voice 3. Alignment: Backbone of the Action 4. Breath: The Great Creative Connector 5. Centred Onset of Sound: The Vocal Identity of the Actor 6. Pitch Range: The Music of Meaning 7. Resonance: Vibrating the Experience 8. Articulation: Shaping Thought and Action Part III: Integrating Voice into the Organic Acting Process 9. Interval: Receiving and Responding 10. Awareness, Ease and Focus 11: The Action: Given Circumstances, Interaction and Objectives 12. Vocal Embodiment of Actions 13. Seeing, Sensing and Feeling 14. Character and Voice 15. The Actor in the Space Part IV: Integrating Voice in Rehearsal and Performance: Putting It All Together 16. Meeting the Play and the Character 17. From Impulse to Action 18. From Action to Form Conclusion Glossary Selected Bibliography -- Index
Revised edition of: Voice into acting : integrating voice and the Stanislavski approach / Christina Gutekunst and John Gillet. 2013.
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Voice culture; Elocution; Method acting; Individual actors & performers; Electronic books